Radiation shielding properties of xPbF2−20Na2O−10CaO−(70−x) B2O3 glass system - Esmail, Abdalla A.S.; M.M, Kassab; M.M, Radwan; M, A. Abd-Latif (Edelweiss Applied Science and Technology, 2025)
The influence of PbF2 incorporation on the physical and radiation shielding properties of six glass samples, labeled BPbF0 to BPbF25, was investigated. These samples have a composition of xPbF2−20Na2O−10CaO−(70−x) B2O3 where (0≤x≤25 in 5 mol.% increments). The physical parameters, including density and molar volume, were calculated. As PbF2 content increased, the density rose significantly from 2.476 g/cm³ to 4.077 g/cm³, attributed to the substitution of low molecular weight B2O3 with high molecular weight PbF2. Similarly, the molar volume increased from 26.95 cm³/mol to 27.138 cm³/mol, indicating the formation of non-bridging oxygen atoms and the expansion of the glass network. X-ray diffraction (XRD) analysis confirmed the amorphous nature of the samples, as no crystalline peaks were observed. Gamma radiation shielding parameters were theoretically evaluated using Phys-X/PSD software. The mass attenuation coefficient (MAC) and linear attenuation coefficient (LAC) were found to increase with higher PbF2 content at a given energy. Both coefficients decreased linearly between 0.015 and 0.08 MeV with increasing energy, remained nearly constant in the range of 1 to 3 MeV due to Compton scattering, and increased gradually beyond 3 MeV due to pair production. The half-value layer (HVL) and mean free path (MFP) decreased as PbF2 content increased, reflecting improved shielding efficiency. Furthermore, the effective atomic number (Zeff) and effective neutron density (Neff) also increased with higher PbF2 content. Compared to commercial glasses like RS-360 and various concretes, the prepared glass system demonstrated superior gamma-ray shielding properties. These findings suggest that the developed glass system is highly effective for gamma radiation shielding applications.